The role of composite financial index in measuring the financial health of higher education - Akidah Fitrah; Dodik Juliardi; Ahmad Priyono (Jurnal Akademi Akuntansi)
Purpose: This research aims to measuring the financial health of state universities in indonesia with the composite financial index.